Five-dimensional f(R) braneworld models - Hoff da Silva, J. M. [UNESP]; Dias, M. (Amer Physical Soc, 2011)
After incorporating f(R) gravity into the general braneworld sum rules scope, it is shown that some particular class of warped five-dimensional nonlinear braneworld models, which may be interesting for the hierarchy problem solution, still require a negative tension brane. For other classes of warp factors (suitable and not suitable for approaching the hierarchy problem) any negative brane tension in the compactification scheme is not necessary. In this vein, it is argued that, in the bulk f(R) gravity context, some types of warp factors may be useful for approaching the hierarchy problem and for evading the necessity of a negative brane tension in the compactification scheme.